PENGEMBANGAN KEPEMIMPINAN SOSIAL-ENTREPRENEURIAL PEMUDA MELALUI PENDAMPINGAN KARANG TARUNA BERBASIS UMKM DALAM MEMPERSIAPKAN GENERASI INDONESIA EMAS - Mawardi; Mona Novita; Doni Aprizal Hadi; Habibissajidin; Mariana; Samsuri (DEVELOPMENT: Journal of Community Engagement, 2024)
Developing social-entrepreneurship-based youth leadership is a crucial strategy for enhancing the capacity of the younger generation to face social and economic challenges toward a Golden Indonesia. However, the role of youth organizations and MSMEs has not yet been optimally integrated into community empowerment practices. This community service activity aims to develop a social-entrepreneurial leadership model through mentoring MSME-based youth organizations (Karang Taruna) using a Participatory Action Research (PAR) approach. The methods used include participatory planning, leadership workshops, MSME mentoring, and collaborative action-reflection involving youth and local businesses as active partners. The results of the activity indicate an increase in the collaborative leadership capacity of youth, strengthening of MSME managerial and digital marketing skills, and the formation of a sustainable community collaboration network. The PAR approach enables experiential learning that encourages social innovation and increases active participant engagement. This program produces an empowerment model based on social-entrepreneurship leadership that has the potential to be replicated in other community contexts as a strategy to strengthen the role of youth and empower the local economy.